2013
DOI: 10.3126/bibechana.v10i0.8454
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the soil corrosivity towards the buried water supply pipelines in Kamerotar town planning area of Bhaktapur, Nepal

Abstract: Soil parameters such as moisture content, pH, resistivity, oxidation-reduction potential, chloride and sulfate ions can give an indication of the soil corrosivity towards the buried-galvanized steels and cast-iron pipelines used to supply the drinking water in Nepal. Present research work was focused to examine such soil parameters collected from Kamerotar town planning area of Bhaktapur district of Nepal. Concentrations of these soil parameters measured in this study are found as: moisture content (18-77%), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The inhibition efficiency of sodium metavanadate for controlling corrosion of carbon steel in an aqueous solution containing chloride ion was evaluated (Sribharathy & Rajendran, 2012). However, a few studies are reported about the corrosion behavior of different steels used in Nepal in aqueous solutions (Bhattarai, 2008(Bhattarai, , 2009Bhattarai et al, 2007) and corrosion of buried corrosive nature of soils towards the galvanized-steel as well as cast-iron pipes used for the drinking water supply in Nepal were also reported by some researchers (Bhandari et al, 2013;Bhattarai et al, 2016;Bhattarai, 2013;Dahal et al, 2014;Dhakal et al, 2014;Gautam and Bhattarai, 2013). In this context, present research work was focused to study the effect of sodium tungstate as a green corrosion inhibitor on the corrosion behavior of the mild steel used Nepal in different aggressive aqueous media.…”
Section: Research Articlementioning
confidence: 90%
“…The inhibition efficiency of sodium metavanadate for controlling corrosion of carbon steel in an aqueous solution containing chloride ion was evaluated (Sribharathy & Rajendran, 2012). However, a few studies are reported about the corrosion behavior of different steels used in Nepal in aqueous solutions (Bhattarai, 2008(Bhattarai, , 2009Bhattarai et al, 2007) and corrosion of buried corrosive nature of soils towards the galvanized-steel as well as cast-iron pipes used for the drinking water supply in Nepal were also reported by some researchers (Bhandari et al, 2013;Bhattarai et al, 2016;Bhattarai, 2013;Dahal et al, 2014;Dhakal et al, 2014;Gautam and Bhattarai, 2013). In this context, present research work was focused to study the effect of sodium tungstate as a green corrosion inhibitor on the corrosion behavior of the mild steel used Nepal in different aggressive aqueous media.…”
Section: Research Articlementioning
confidence: 90%
“…Gravimetric method was used to estimate the amounts of sulfate content in soil samples. The details of these all methods are also discussed elsewhere (Dahal et al, 2014;Dhakal et al, 2014;Bhandari et al, 2013;Bhattarai, 2013aBhattarai, , 2013bGautam & Bhattarai, 2013;Bhattarai et al, 2016).…”
Section: Fig 1 Satellite Map Of Sampling Areamentioning
confidence: 99%
“…A detailed study about the properties of porcelain raw materials deposited in Pachamane (Shivapuri conservation area of Kathmandu district) and Daman (Makawanpur district) areas of Nepal was carried out since the 1990s [9,32,[41][42][43]. However, there are no detailed research works carried out yet on the geological genesis study of the natural white clay minerals deposited in the Thimi area of Bhaktapur, except their corrosive behavior to the buried-metallic pipelines [44,45], and adsorption characteristics [18]. In this context, the present work aimed to explore the geological genesis of the Thimi white clays based on their qualitative and quantitative data analyses.…”
Section: Introductionmentioning
confidence: 99%